Preliminary study on humidity effect of solid state lighting (SSL) - Xiong, Meng. (2010)
Solid State Lighting (SSL) has become a promising light source for the replacement of conventional lighting sources, which has been actively developed on many commercial applications. Hence it is important to evaluate and understand the failures mechanisms that affect the performance characteristics and lifetime of SSL. There are various factors (voltage, current, junction temperature, humidity) affecting the SSL lifetime but little work has been on humidity effect; hence our study concerns the humidity effect on the degradation of SSL. To study the humidity effect on SSL, a humidity model is required to build relating the failure time to different humidity levels. There are two problems faced in building a humidity model. Firstly, a life-time extrapolation is required to establish a humidity model. However, the life extrapolation without the knowledge of failure mechanism will be difficult. Secondly, present humidity models are mainly based on corrosion mechanism, but preliminary study found that LED’s failure is not corrosion related. Hence this project is to design a humidity accelerated life test and investigate the failure mechanism due to humidity effect, which acts as the basis for developing a humidity model for SSL so that one can perform the extrapolation and hence able to predict SSL lifetime under different humidity levels.